DEMOGRAPHICS OF BASAL CELL CARCINOMA AND ITS SURGICAL MANAGEMENT - Afridi, Riaz Ahmed Khan; Ahmed, Ehtisham; Khan, Shahbaz Ali; Ali, Asghar (Journal of Ayub Medical College Abbottabad, 2012)
Background: Basal cell carcinoma (BCC) is the most common, slow growing epidermal skin tumour and an increase in its incidence has been noticed in the past decades. Different treatment options include surgical and non-surgical measures. Surgical options include surgical excision, cryosurgery, curettage, electrodessication and Mohs micrographic surgery. Non-surgical treatments options are 5- flourouracil, photodynamic therapy, immunomodulation and radiotherapy. This study was conducted to determine the demographics of facial BCC and its rate of incomplete excision and recurrence. Methods: Clinically diagnosed facial BCCs were included in this prospective descriptive study. Tumours were excised with 3-5 mm clinically palpable safe margins and were sent for histopathological confirmation and margin clearance. All patients were followed for a minimum of two years to look for any recurrence. The demographic data, site, clinical presentation, size of the lesion, excision margins, reconstructive options, complications, histopathological margin clearance and recurrence was recorded and analysed. Results: A total of 139 cases were recruited in this study. Four cases were lost in follow-up. Out of remaining 135 patients including 78 males and 57 females with a mean age of 58.6 years were studied. The commonest site of involvement was nose (45.9%), followed by periocular (28.1%) and cheek (15.6%) regions. The most common clinical type was nodular (51%) followed by ulcerative (38.5%). In majority of the cases, the resulting defect after excision was reconstructed with local flaps (57.8%). Majority (77.8%) of tumours had histopathologically clear margins while 20% had tumour involvement. During 2 years follow-up period, 8.9% patients had tumour recurrence. Keywords: Basal cell carcinoma, excision, recurrence, tumour